Topics on the Na+/Ca2+ Exchanger: Pharmacological Characterization of Na+/Ca2+ Exchanger Inhibitors - Yasuhide Watanabe; Yuuki Koide; Junko Kimura (Elsevier, 2006)
Using the whole-cell voltage clamp, we examined acute effects of various agents on Na+/Ca2+ exchange current (INCX) in guinea-pig cardiac ventricular cells and transfected cells. Among the antiarrhythmic drugs, amiodarone, bepridil, dronedarone, cibenzoline, azimilide, and aprindine inhibited INCX in a concentration-dependent manner. We also investigated the effects on NCX of 2,3-buanedione monoxim (BDM) and selective NCX inhibitors such as KB-R7943, SEA0400, and SN-6. The presence of trypsin in the pipette solution attenuated the inhibitory effects on NCX of amiodarone, bepridil, and BDM, suggesting that these drugs inhibit NCX from the cytosolic side. In contrast, the trypsin-insensitive NCX inhibitors were aprindine, azimilide, dronedarone, cibenzoline, KB-R7943, SEA0400, and SN-6. KB-R7943, SEA0400, and SN-6 suppressed the uni-directional outward INCX more potently than the uni-directional inward INCX. The mechanism of this mode-dependency is unknown, but is suggested to be related to intracellular Na+ concentration. Keywords:: antiarrhythmic drug, benzyloxyphenyl analogue, blocker, Na+/Ca2+ exchange current, pharmacophore model